PELAKSANAAN KOMUNIKASI EFEKTIF MAHASISWA DAN DOSEN DALAM PENYELESAIAN SKRIPSI DI PROGRAM STUDI KOMUNIKASI DAN PENYIARAN ISLAM UNIVERSITAS ISLAM NEGERI SJECH M.DJAMIL DJAMBEK BUKITTINGGI - Risma Aziza; Yusuf Afandi; Khairuddin Khairuddin; Tomi Hendra (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of this research is to see the ability of KPI Study Program students in implementing effective communication in the thesis completion process. This type of research is a field research (Field Research) with a qualitative approach that describes what is about a situation. In this study, the authors describe the implementation of effective communication between students and lecturers in the process of completing the thesis at the Islamic Communication and Broadcasting Study Program, State Islamic University Sjech M.Djamil Djambek Bukittinggi. Based on the results of the study, it can be concluded that the implementation of effective communication between students and lecturers that is applied or carried out in the process of completing the thesis is said to be good. So that there is a reciprocal relationship between the communicant and the communicator in the continuity of the thesis completion process. The application of effective communication applied by students of the Islamic Communication and Broadcasting Study Program and lecturers at the State Islamic University of Sjech M. Djamil Djambek Bukittinggi in the process of completing student thesis, among others, by paying attention to the condition of the communicant. themselves, convey the content of the message in the form of language that is easy to understand and understand. , making short points in communication, explaining the intent and purpose before interacting, accompanied by body language so that the message can be conveyed properly, using ethics in communicating and also paying attention and listening to the other person when communicating and using media to support communication. continuation of the thesis completion process. Keywords: Implementation of Effective Communication, Students, Lecturers, Thesis, KPI